Why do accounting students at higher learning institutions conduct an academic dishonesty? - Mustikarini, Arizona; Winardi, Rijadh Djatu; Azalea, Maria (2017)
Academic dishonesty is a serious educational problem.Moreover, the tendency to cheat at workplace appertain with the frequency of cheating in college.This study aims to empirically examine the influence of individual factors and situational factors to the intention of accounting students to conduct an academic dishonesty.This study uses survey as data collection technique by employing a set of a questionnaire.This result of this research finds that attitudes, subjective norms, and perceived behavioural control have positive and significant effects to the intention of the accounting students to commit an academic dishonesty.However, among three situational factors only pressure and definitional ambiguity that have a positive and significant effect to the intention of accounting students.